Severe arterial thrombosis associated with Covid-19 infection. Issue 192 (August 2020) - Kashi, Mahine; Jacquin, Aurélien; Dakhil, Bassel; Zaimi, Rym; Mahé, Emmanuel; Tella, Emilie; Bagan, Patrick
Highlights: Unlike venous thromboembolism, no data are available on arterial thrombosis in SARS-CoV2 infected patients. We observed severe arterial thrombotic complications despite the use of antiplatelet or anticoagulant therapy. We described five irreversible lower limb ischemia and two thoracic aortic free floating thrombi. Further studies are needed to evaluate the necessity of therapeutic anticoagulation in COVID-19 patients.